1999
DOI: 10.1677/joe.0.1620341
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor expression of proliferating basal and luminal cells in adult murine ventral prostate

Abstract: Maintenance of the size and differentiated function of the adult prostate is dependent on testicular androgens. In this study, simultaneous androgen receptor (AR) immunohistochemistry and [3 H]thymidine labelling was used to characterise the proliferating epithelial cells of the murine ventral prostate. Proliferation in the adult prostate was more prevalent in the basal cell population with 1·8% AR-negative cells labelled with [3 H]thymidine as compared with 0·7% AR-expressing luminal cells. Three weeks follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 32 publications
1
43
0
2
Order By: Relevance
“…Most studies in the human report AR expression is restricted to the luminal cell layer; several studies in the mouse report widespread expression in both basal and luminal cells (16)(17)(18). qPCR and Western blot analyses demonstrate that both mRNA and protein for AR can be identified at high levels in basal/stem, luminal, and stromal cell fractions ( Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Most studies in the human report AR expression is restricted to the luminal cell layer; several studies in the mouse report widespread expression in both basal and luminal cells (16)(17)(18). qPCR and Western blot analyses demonstrate that both mRNA and protein for AR can be identified at high levels in basal/stem, luminal, and stromal cell fractions ( Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Luminal cells express high levels of AR and respond directly to androgens by stimulating production and secretion of prostatic differentiation markers. Basal cells are usually considered to lack AR expression, but several studies have reported AR localization using immunohistochemistry in a subset of basal cells in normal human and rodent prostate specimens as well as hyperplastic human prostate samples (Bonkhoff & Remberger 1993, Mirosevich et al 1999 (Mirosevich et al 1999, Lee et al 2012. The disposition of the androgen/AR signaling axis in these cells likely influences future prostate cancer development.…”
Section: Androgens and Ar In Prostate Development And Homeostasismentioning
confidence: 99%
“…The marked increase in prostate growth during puberty is largely attributable to a strong proliferation of luminal prostate cells, with the majority of basal cells remaining inactive [80]. [ 3 H] thymidine uptake studies showed that basal cells with high levels of AR are not actively involved in proliferation [84]. In addition, the recent discovery of a luminal-restricted progenitor cell population in the mammary gland supports the concept of separate basal-and luminal-derived progenitor cell populations responding independently to various growth and differentiation cues [85].…”
Section: Prostate Stem/progenitor Cells and Cscsmentioning
confidence: 99%